An Analytical Review of Orientation Based Concurrency Control Algorithm (Global Journal of Computer Science and Technology, 2011)
There is an ever-increasing demand for higher throughputs in transaction processing systems leading to higher degrees of transaction concurrency.Concurrency control in Database management systems ensures that database transactions are performed concurrently without violating the data integrity of the database. Thus concurrency control is an essential element for correctness in any system where two database transactions or more, executed with time overlap, can access the same data. There are problems like Deadlock,Livelock and prevention of these problems is vital in concurrency control of distributed database systems.Many techniques have been proposed for managing concurrent execution of transactions in database systems.A new method for concurrency control in distributed DBMS2019;s,is discussed which will improve system performance by reducing the chances of deadlock and livelock and reducing restart ratio.
Keywords: concurrency; deadlock; timestamp; lock etc